Recognizing Panulirus meripurpuratus sp. nov. (Decapoda: Palinuridae) in Brazil—Systematic and biogeographic overview of Panulirus species in the Atlantic Ocean - Giraldes, Bruno Welter; Smyth, David Mark (Zootaxa, 2016)
Genetic analysis divides Panulirus argus into two different species, physically separated by the Amazon-Orinoco plume since the Last Glacial Maximum. Panulirus argus sensu stricto is distributed north of this biogeographic barrier and the second species to the south, occurring in Brazil. The Panulirus species in the Atlantic Ocean are being overfished and the standing stocks are unknown and still not considered endangered or threatened due to a deficiency of precise abundance data. The lack of data makes it impossible to undertake an effective conservation and management policy. In order to assist in the future management and conservation of the Spiny Lobster in the Atlantic Ocean and particularly for the indigenous species from Brazilian waters, this study formally recognizes and describes a new species, Panulirus meripurpuratus sp. nov., for what was previously known as P. argus in Brazilian waters, and differentiates it from Panulirus argus from North American waters and the Caribbean Sea. The work also presents an overview of the biogeographic distribution of the species and presents two identification keys to Atlantic species, one based on morphology and the other on live colouration.